The Differences of Group learning in the Classroom-based and the Web-based Environments: Factor Analysis - Zhao, Jianhua; McConnell, David (Proceedings of the International Conference on Networked Learning, 2006)
The purpose of this study is to examine the differences of group learning (GL) in the classroom-based and the web-based environments through factor analysis. Our previous study has already identified 62 influencing factors of a GL process according to the content analysis from the literature. 276 teachers participated in a well-structured questionnaire survey and the data were analysed by SPSS. Four main factors were extracted and ranked according to their weightings. The findings reveal that there are differences of GL between these two environments, and two main factors are in the different positions for different environments. The interdependent relationship of these four main factors is described as a framework of a GL process.